Tabela de vida das culturas para o feijoeiro (Phaseolus vulgaris L.), com ênfase nas pragas e seus danos, em três plantios no período da seca - C P Calil, Antonio; Chandler, Leland; B Nogueira, Sebastião; W D Casali, Vicente; Domingos Galvão, José (Revista Ceres, 2025)
Three dry season plantings of beans (Phaseolus vulgaris L.) were made at approximately three-week intervals (February 6, 28 and March 20, 1981) at Viçosa, MG, to observe the development and evaluate the importance of the insect pests.